Pangan Lokal (Granola Moringa) Sebagai Makanan Tambahan Pencegah Stunting Pada Balita Gizi Kurang di Puskesmas Dompu Barat Kabupaten Dompu - Andriani, Mardian; Hairunis, Mirham Nurul; Qamarya, Nurul; Faturahmah, Erni; Juniarti, Windaz (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2023)
UNICEF explained that if nutrition problems are not taken care of properly during the Covid-19 pandemic, there will be a 15% increase in the number of children <5 years old who experience acute malnutrition can increase the risk of stunting. The stunting data in NTB (2020) is 20.9%, where the highest stunting data is in West Lombok Regency (29.3%), and the lowest is in Bima City (7.9%). Dompu Regency ranks 5th at 25%, whereas Woja District is the area with the highest stunting incidence in 2020 is 54.98%. Based on e-PPGBM data (2020) in Woja District, there are 3rd villages with the highest stunting rate, namely Matua Village 82.04%, Monta Baru Village 61.9%, and Rababaka Village 60.71%. This study aims to analyze the nutritional benefits of supplementary feeding with granola moringa in undernourished children; measure and analyze changes in the nutritional status and development of children; prepare recommendations for the sustainability of the granola moringa supplementary food program with the Dompu Barat Health Center. The research method uses quantitative methods with a quasi-experimental approach with a control group. The data collection instruments were interview guides and observation sheets. Data analysis used the sample paired t-test. The results of the test of paired sample t-test obtained a sig value. (2-tailed) is 0.001 < 0.05 with t value -10.456 > t table 2 means that there is a difference in the average weight of children after being given granola moringa, which means that there is an effect of local food (granola moringa) as additional food for stunting prevention in malnutrition toddlers and the effectiveness of giving granola moringa was 0.4 (medium category).